2023
DOI: 10.1152/jn.00156.2023
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture in the treatment of IBS in rats: investigation of the mechanisms of CRH+ neurons in the paraventricular nucleus

Abstract: Electroacupuncture (EA) is well documented to treat irritable bowel syndrome (IBS). However, the mechanism of the central nervous system related to IBS and acupuncture stimulation is still not well known. In this study, a rat model of IBS was established by cold-restraint comprehensive stresses for 15 days, and it was found that the levels of corticotropin-releasing hormone (CRH), corticosterone (CORT), and adrenocorticotropic hormone (ACTH) in the peripheral serum were increased; the visceral sensitivity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous evidence has shown that the expression of PVN c-Fos, pituitary and plasma CRH, ACTH and cortisol increase in rodents with visceral hypersensitivity, indicating that the HPA axis is activated 114 , 150 – 153 . Additionally, stress-induced activation or enhancement of the CRH and HPA axis systems is associated with visceral hypersensitivity, which is an important feature of IBS.…”
Section: Pvnmentioning
confidence: 99%
“…Previous evidence has shown that the expression of PVN c-Fos, pituitary and plasma CRH, ACTH and cortisol increase in rodents with visceral hypersensitivity, indicating that the HPA axis is activated 114 , 150 – 153 . Additionally, stress-induced activation or enhancement of the CRH and HPA axis systems is associated with visceral hypersensitivity, which is an important feature of IBS.…”
Section: Pvnmentioning
confidence: 99%